1999
DOI: 10.1021/bi991573v
|View full text |Cite
|
Sign up to set email alerts
|

CTP:Phosphocholine Cytidylyltransferase Activation by Oxidized Phosphatidylcholines Correlates with a Decrease in Lipid Order:  A 2H NMR Analysis

Abstract: The enzyme CTP:phosphocholine cytidylyltransferase (CT) binds reversibly to membranes and is active only in its membrane-bound form. Membrane lipid composition influences the equilibrium between its soluble and membrane-bound forms. Whereas the enzyme is not activated by phosphatidylcholine (PC) vesicles, it is activated by PC vesicles that have been oxidized with HClO(4) [Drobnies, A. E., et al. (1998) Biochim. Biophys. Acta 1393, 90-98]. Here we explore the mechanism of activation of CT by a PC oxidized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Aging and oxidative stress both caused up-regulation of Cct-1, which encodes the rate limiting enzyme in phosphatidylcholine synthesis (33). Cct-1 enzyme is activated by oxidized lipids (34), and Cct-1 gene expression level may affect Drosophila life span (35). Aging and oxidative stress responses also shared the down-regulation of numerous proteasome subunits and other proteases (41 genes), alkaline phosphatases (eight genes), and triacylglycerol lipases (four genes).…”
Section: Resultsmentioning
confidence: 99%
“…Aging and oxidative stress both caused up-regulation of Cct-1, which encodes the rate limiting enzyme in phosphatidylcholine synthesis (33). Cct-1 enzyme is activated by oxidized lipids (34), and Cct-1 gene expression level may affect Drosophila life span (35). Aging and oxidative stress responses also shared the down-regulation of numerous proteasome subunits and other proteases (41 genes), alkaline phosphatases (eight genes), and triacylglycerol lipases (four genes).…”
Section: Resultsmentioning
confidence: 99%
“…M domain peptides from rat CCTa [200][201][202] and P. falciparum CCT [203] also bind selectively to anionic lipid Loop L2 75 122 vesicles. Activation of rat CCTa by vesicles containing DAG, unsaturated PEs, oxidized PCs, fatty alcohol, oxysterols, and farnesol has also been reported [184,186,192,193,204,205]. This latter group of lipids can be categorized as type II non-bilayer forming lipids that promote negative curvature strain when mixed with bilayer-stabilizing phospholipids [206].…”
Section: In Vitro Analysis Of Membrane Binding With Purified Cctmentioning
confidence: 94%
“…3), because mitochondrial GPAT plays a key role in establishing initial asymmetric distribution of saturated and unsaturated FA in PL (1,36) and its deficiency was shown to decrease 16:0 and increase 20:4 contents in hepatic PC and PE (38). Given that insertion of CCT into membrane was shown to be enhanced by polyunsaturated fatty acids (39), increased unsaturated PE level (20,37), and by disordered fatty acyl chains of PL (25,26) in vitro, alterations in PL fatty acid composition and its membrane organization due to Scd1 mutation might directly promote CCT membrane binding. Indeed, recent confocal microscopy studies have revealed that Scd expression is a very potent regulator of membrane domain structure (40).…”
Section: Cdp-choline Pathway Of Pc Synthesis Is Up-regulated Whereasmentioning
confidence: 99%
“…One well characterized mode of regulation of CCT activity is through translocation of the protein from an inactive, soluble form to an active, membrane-bound form (20,22). The insertion of CCT into membranes has been shown to increase by the properties of membranes, including loose packing of lipids in the membrane (23), curvature strain (24), and changes in the fatty acid composition of PL (25,26). Because oleic acid is the most abundant monounsaturated fatty acid in mammalian PL, we hypothesized that membrane perturbation that might occur as a consequence of Scd1 deficiency would affect CCT translocation into membranes, and thus SCD might play an important role in regulating PC biosynthesis.…”
mentioning
confidence: 99%